Mekong Basin Focal Project: Synthesis report - Kirby, M.; Krittasudthacheewa, C.; Mainuddin, M.; Kemp-Benedict, Eric; Swartz, C.; Rosa, E. de la (CGIAR Challenge Program on Water and Food, 2009)
The Mekong Basin Focal Project aims were to assess water use, water productivity and water poverty in the basin, and analyse the opportunities and risks of change in water management that influences water poverty. The main issue facing the Lower Mekong is not water availability (except for seasonally in certain areas such as northeast Thailand) but the impact of changed flows (which may result from dam or irrigation development or climate change) on ecology, fish production, access to water and food security. Poverty is generally decreasing in the Mekong, but the poorer people are not sharing in the improvements. Water governance and sharing of benefits is a key challenge for the Mekong.